We Read but How: Research on Reading and Reading Comprehension Skills - Mehmet Arif Bozan (e-Kafkas Eğitim Araştırmaları Dergisi, 2024)
Reading and reading comprehension skills are among the most basic language skills. Therefore, these skills should be acquired at an early age. Although there are studies in terms of reading in Türkiye, it was seen that reading comprehension skills are insufficient in the exams. This study investigated how reading and reading comprehension activities were carried out at the primary school level and how this situation reflected on students. This study was designed as a case study to reveal the subject to be examined in depth. The participant group of this study, which was carried out at the primary school level, consisted of 207 students and eight primary school teachers. Data were collected from students with a reading comprehension test and teachers with a semi-structured interview form. The data obtained from the achievement test are presented descriptively. The interviews with the teachers were analyzed by content analysis. According to the data obtained, it was seen that the teachers preferred the reward method in gaining the habit of reading, and they carried out activities that would improve the students' cognitive skills for their reading comprehension skills. The result that 70.53% of the students in the research made the profound understanding question wrong was also a remarkable situation.